2022
DOI: 10.21203/rs.3.rs-1700325/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

METTL3 affects FLT3-ITD+ Acute Myeloid Leukemia by mediating autophagy by regulating PSMA3-AS1 stability

Abstract: Objective The study was designed to explore the role of PSMA3-AS1 in initiation and progression of acute myeloid leukemia (AML) and investigate its action mechanism. Methods Expression of PSMA3-AS1, miR-20a-5p and ATG16L1 both in vitro and in vivo was measured by qRT-PCR. The expression of protein was detected by western blot assay. Edu staining and flow cytometry were utilized to measure cell proliferation and apoptosis. Potential target was predicted by bioinformatics and was verified by dual-luciferase re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Through RNA-seq and MeRIP-seq analyses, we identified a prominent m 6 A site in the 3′UTR of PDE3A mRNA. Silencing METTL3 significantly downregulated the methylation peak of this site, indicating that METTL3 mediates m 6 A modification of the adenosine in the GGACC sequence of the PDE3A 3′UTR, potentially leading to PDE3A mRNA degradation. Mechanistic experiments demonstrated that METTL3 regulates m 6 A methylation at the A residue within the GGACC motif of the PDE3A 3′UTR.…”
Section: Mettl3 Regulates Pde3a Mrna Stability Through Ythdf3mentioning
confidence: 99%
See 4 more Smart Citations
“…Through RNA-seq and MeRIP-seq analyses, we identified a prominent m 6 A site in the 3′UTR of PDE3A mRNA. Silencing METTL3 significantly downregulated the methylation peak of this site, indicating that METTL3 mediates m 6 A modification of the adenosine in the GGACC sequence of the PDE3A 3′UTR, potentially leading to PDE3A mRNA degradation. Mechanistic experiments demonstrated that METTL3 regulates m 6 A methylation at the A residue within the GGACC motif of the PDE3A 3′UTR.…”
Section: Mettl3 Regulates Pde3a Mrna Stability Through Ythdf3mentioning
confidence: 99%
“…Only PDE3A a notably high enrichment (≥2000), warranting further investigation. MeRIP-seq revealed that the consensus motif of METTL3 was recognized during m 6 A modification (GGACC) of the 3′ untranslated region (UTR) of PDE3A mRNA (Figure 7G). Therefore, PDE3A may be a potential target gene for METTL3-mediated m 6 A modification.…”
Section: Merip-seq Combined With Rna-seq Identified Pde3a As a Target...mentioning
confidence: 99%
See 3 more Smart Citations